Evaluación del crecimiento de café y cacao, tratado con 3 aplicaciones de biol, enriquecido con sustancias orgánicas en la producción de plantones en Lamas - Rojas Gonzales, Jardy Luis (2014)
In the Lamas city, Benzaken founded, from July 10,2013 to March 20,2014, the project of investigation developed "assessment of the growth of "coffee" and "cocoa" treaty with three applications of Biol, enriched with organic substances in the production of seedlings in Lamas - 2014 ". The specific objectives were to perform applications of Biol enriched with bee honey, coconut milk and cow milk, using three frequencies, in the production of seedlings of "coffee and cocoa", and perform the biometric evaluations of plant organs of the seedlings of the coffee and cocoa, until the optimal stage for the fmal field location. The wording of the problem was: How is the coffee growth and cocoa treated in three frequencies of applications of Biol enriched with organic substances, in the production of seedlings in Lamas, between the variables proposed the independent variable was frequency of applications of Biol and the dependent variable was growth and development of the seedlings of "coffee" and "cocoa". To demonstrate the hypothesis was ifthe applications ofBiol enriched with organic substances, influence in the plants growth and development, then there will be significance between the three frequencies of a Biol application, used in the growth and development of seedlings of "coffee" and "cocoa" in Lamas. The treatments under study were AO (Light}, Al (01 application), A2 (02 applications}, A3 (03 applications). The results were as shown in the following conclusions: In the cocoa, the greatest height reached the treatment A3 (three applications) with 15.53 cm, followed by Al (an application) with 14.90 cm and A2 (two applications) with 13.95 cm, surpassing the witness (AO) with 13.1 cm. In the sheets number of coffee was the largest value of the treatment A2 (two applications) with 2.37 units, followed by the A3 (three applications) with 2.33 units, the Al (an application) with 2.32 units and fmally the witness AO with 2.25 units. The number of cocoa sheets rose to measure that increased foliar applications ofthe Biol prepared. The treatment A3 (three applications) was higher with 2.44 sheets, the treatment A2 (two applications) with 2.38 sheets, the treatment Al (an application) with 2.36 and fmally the AO (witness) with 2.24 sheets. Finally, with the processing of the data obtained in the evaluations and through in an OVA and the Duncan test with 0.05 level of probability, we reject the hypothesis proposed. Key words: biometric evaluations; organic substances.